2016
DOI: 10.1016/j.rbmo.2015.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic studies of 1232 patients with different sexual development abnormalities from the Sultanate of Oman

Abstract: The aim of this study was to evaluate cytogenetic findings in Omani patients who had been referred for suspicion of sex chromosome abnormalities that resulted in different clinical disorders. Furthermore, it sought to examine the frequency of chromosomal anomalies in these patients and to compare the obtained results with those reported elsewhere. Cytogenetic analysis was performed on 1232 cases with variant characteristics of sexual development disorders who had been referred to the cytogenetic department, Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Comparing our results with other studies, the frequency of chromosomal abnormalities identified in this study (7.13%) is in accordance ( p > .05) with the frequencies reported in Saudi Arabia (4.4%) (Husain & Zaki, ) and in Sultanate of Oman (10.07%) (Al‐Alawi, Goud, Al‐Harasi, & Rajab, ), and is less frequent than the frequency reported in Turkey (13.6%) (Balkan et al, ) (Figure ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Comparing our results with other studies, the frequency of chromosomal abnormalities identified in this study (7.13%) is in accordance ( p > .05) with the frequencies reported in Saudi Arabia (4.4%) (Husain & Zaki, ) and in Sultanate of Oman (10.07%) (Al‐Alawi, Goud, Al‐Harasi, & Rajab, ), and is less frequent than the frequency reported in Turkey (13.6%) (Balkan et al, ) (Figure ).…”
Section: Resultssupporting
confidence: 91%
“…It is characterized by the presence of small testes, lack of sperm development, and late puberty with diminished secondary sexual characteristics. The physique is usually fine and elongated with sometimes gynecomastia (Al‐Alawi et al, ). However, the XXY karyotype was identified in 18 patients with AG, while XXYY,22ps+ and X/X,idic(Y)/XXY karyotypes were observed in one patient each with AG.…”
Section: Resultsmentioning
confidence: 99%
“…The two most common etiologies for PA were MRKH (n = 14, 23.3%) and gonadal dysgenesis (8,13.33%), and three patients were diagnosed with 46, XY. One had Sweyer's syndrome, and two patients had androgen insensitivity syndrome (AIS) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the significant impact on sexual ambiguity, delayed puberty, amenorrhea and infertility is well known. 8 Karyotyping is particularly crucial for patients with PA. It allows for appropriate diagnosis and management as further testing (including fluorescent in situ hybridization [FISH] and comparative genomic hybridization) may also be needed.…”
Section: Introductionmentioning
confidence: 99%
“…The basal level of T varies widely in the population; therefore, the ratio of the T/LH is considered a better parameter for evaluating male gonad function. Also, in the early stage of hypogonadism, T production may be decreased which cause the increase of LH and finally change the T/LH ratio [ 111 , 112 ].…”
Section: Sars-cov-2 Virus and Male Hormonesmentioning
confidence: 99%